Use of Brain-based Learning Strategies in the Teaching of Literature Component to Low Ability ESL Learners - Albert, Wilson; Joseph, Ramanair; SOUBAKEAVATHI, RETHINASAMY (University of Putra Malaysia, 2024)
Brain-based learning (BBL) has the potential to improve learner’s engagement and learning outcome in English Language learning. While many studies have been conducted in various parts of the world, studies on BBL in Malaysia especially in relation to English language learning is scarce. The problem examined in this study was two-fold. First, previous studies in the Malaysian ESL literature component lessons revealed that the lessons were considered uninteresting and did not sufficiently engage the learners. Although teachers have been trained in BBL, there has been little to no follow-up concerning if and how they are implementing brain-based strategies. Despite claims that brain-based learning strategies improve learner success, the extent to which teachers implement brain-based strategies in different contexts is unknown. Second, previous BBL studies conducted in Malaysia is currently limited to other school subjects. There appears to be a lack of research on Malaysian low ability ESL learners’ performance and responses after BBL implementation. This study intends to narrow these gaps, and the aim is to investigate the use of BBL strategies among low ability Malaysian ESL learners. The theoretical and conceptual framework was adapted from BBL and Constructivist learning principles. The design for this study was both quantitative and qualitative. The quantitative described the 150 upper secondary school low ability L2 learners’ performance in a literature response writing test. The qualitative design employed semi-structured interviews and classroom observations. Six ESL teachers teaching these learners were also involved. The non-participant classroom observation and semi-structured interviews were conducted to these six teachers. Separate interviews were also conducted to three learner focus groups. After a six-week BBL implementation, a pair samples t-test showed that there was a statistically significant improvement in the literature component essay writing scores from the pretest (M=2.45, SD=1.50) to the post-test (M=5.35, SD=2.40), t(149)= -15.48, p< .05. An inductive thematic analysis on the classroom observations and the participants’ responses revealed that there were positive responses to the four BBL theoretical components of this study’s framework– experiential learning, individual differences, search for meaning through patterning and the brain processes the whole and parts simultaneously. However, two components - learning that is low in threat but high in challenge and positive social interactions yielded mixed responses. The negative responses were largely attributed to the learners’ limited ESL proficiency. This study indicates that BBL was able to enhance low ability ESL learners’ writing performance, meaningful learning, and active learning engagement.